The Influence of Indigenous Oral Storytelling on Western Literary Forms: A Study of Joy Harjo’s Poetic Narratives - Glyal, Mohanad Ghanim (Technium Education and Humanities, 2025)
This postcolonial deconstructive analysis of American Indian literature builds on hard postcolonial theoretical work. However, it also places very much emphasis on the often-oral tradition of a large portion of American Indian literatures. The works of Joy Harjo are only a small part of this tradition, which separates it from other postcolonial literatures. My essay attempts to make new statements about the importance of American Indian storytelling, particularly as developed in Harjo’s poetic narratives. I hope to provide some diverse and inspired reading of Harjo’s poetry, looking at the influences that the organic fusion of the oral and written traditions has on postcolonial writing. As with much postcolonial writing, the difficulty with Harjo’s varied poetry is that it is not glaringly postcolonial in the traditional sense or even, as critics concerned with postcolonial literatures show, in a wider presence of the other in mainstream literature. But it is perhaps such integrated cultural voices that will make the more political aspects of Harjo’s writing more meaningful to others who might not be used to her postcolonial context. This essay focuses on the influence of oral storytelling traditions of Indigenous peoples on Western literary forms, with a particular focus on Joy Harjo’s use of poetic narratives. It suggests that a blending or merging of approaches towards different modes of narration, as seen in Harjo’s poetics, allows a possibility for new articulations of old stories to emanate. Such efforts facilitate the creation of a space that can voice the thoughts, feelings, and attitudes of the present.